Responses of female reproductive hormones and histopathology in the reproductive organs and associated lymph nodes of Boer does challenged with Corynebacterium pseudotuberculosis and its immunogenic corynomycolic acid extract - Jesse, Faez Firdaus Abdullah; Odhah, Mohammed Naji; Abba, Yusuf; Garba, Bashiru (Academic Press, 2020)
Corynebacterium pseudotuberculosis biotype ovis is a bacterium that causes caseous lymphadenitis (CLA), a chronic disease of sheep and goats characterized by the formation of suppurative abscesses in superficial and visceral lymph nodes and internal organs of small ruminants. This study was designed to evaluate the reproductive hormonal changes (estrogen and progesterone) and histopathology in the reproductive organs and associated lymph nodes of does challenged with C. pseudotuberculosis biotype ovis and its immunogen; corynomycolic acid. A total of 12 healthy non-pregnant female goats were grouped into three: A, B and C consisting of four does each. Group A was intradermally inoculated with 2 mL of sterile phosphate buffered saline (PBS) pH 7 (negative control group); group B was intradermally inoculated with 2 mL of corynomycolic acid extract (CMAs), while group C was intradermally inoculated with 2 mL of 10⁹ colony-forming unit (cfu) of live C. pseudotuberculosis. Blood samples were also collected at predetermined intervals for estrogen and progesterone hormonal assays. The does were euthanized 90 days post challenge and tissue samples of the uterus, ovaries, fallopian tubes, cervix and associated lymph nodes were collected and fixed in 10% neutral buffered formalin for histopathological processing. The result showed various degrees of histopathological changes (hemorrhage, congestion, degeneration, necrosis, edema, leucocytic infiltrations) in the reproductive organs and associated lymph nodes of both inoculation groups. Increases in estrogen hormone concentration were observed in both inoculation groups in comparison to the control group. However, progesterone concentration was only increased in group C. This study highlighted that corynomycolic acid extract from C. pseudotuberculosis biotype ovis resulted in significant histopathology in the reproductive organs and associated lymph nodes of does and increase estrogen concentration.